Koefisien beban pokok atas kinerja laba usaha - Kezia Fricilia Toniga; Winston Pontoh; Meily Y. B. Kalalo (Yayasan Widyantara Nawasena Raharja, 2026)
This study investigates the effect of the cost coefficient, defined as the ratio of cost of goods sold to revenue, on operating profit performance in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. The research employs a quantitative approach using simple linear regression. The sample comprises 43 companies, yielding 129 observations obtained via purposive sampling. The results reveal that the cost coefficient has a positive and significant effect on operating profit, although it explains only 3.8% of the variation. This implies that cost efficiency remains a critical factor for improving operating performance despite other influencing variables. This study contributes by providing empirical evidence on the importance of cost efficiency in non-cyclical sectors, which are often considered stable but still sensitive to production cost management.